Needs assessment model for problem-based preschool curriculum - Esperon, Maria Christina C. (2005)
The Problem-Based Curriculum (PBC) is a current trend being highly researched in countries like Japan, the US, and the UK in their educational systems from preschool to tertiary level. This study aimed to develop a needs assessment model for the design of a PBC for preschools. Three phases of research, namely, a documentary analysis, a preconstruction of the model, and improvement and validation of this model were undertaken to achieve this goal. Results showed that both the framework and the procedure focus on the learner. To select good units of problems for the PBC for preschool, the following criteria were found significant for the selection process: relevance, real, contextualized, significance, and embedded targets.
Thesis (M.A. Curriculum Studies)--University of the Philippines, Diliman.
Keywords: Education, Preschool -- Curricula -- Philippines; Curriculum planning -- Philippines